2023
DOI: 10.1021/acsnano.2c10103
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated MXene Nanosheets for Integrated Bone–Soft Tissue Therapy: Effect and Potential Mechanism

Abstract: The bone defects caused by trauma are inevitably accompanied by soft tissue damage. The development of multifunctional bioactive biomaterials with integrated bone and soft tissue regeneration is necessary and needed urgently in orthopedics. In this work, we found that the photoactivated MXene (Ti3C2T x ) nanosheet showed positive effects on promoting both bone and soft tissue regeneration. We further investigated the detailed effect and potential mechanism of photoactivated MXene on tissue regeneration. Photoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Reproduced with permission. [ 223 ] Copyright 2023, ACS. c) Schematic of ultrasonic bactericidal mechanism for BiFeO 3 /Ti 3 C 2 .…”
Section: Technological Prospects Of Mxenesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 223 ] Copyright 2023, ACS. c) Schematic of ultrasonic bactericidal mechanism for BiFeO 3 /Ti 3 C 2 .…”
Section: Technological Prospects Of Mxenesmentioning
confidence: 99%
“…Qu et al. [ 223 ] demonstrated the photo‐activation of Ti 3 C 2 T x MXene nanosheets for the inhibition of methicillin‐resistant Staphylococcus aureus (MRSA) using PTT (Figure 19b). Additionally, they induced the expression of pro‐angiogenic factors (VEGF and CD31) to promote soft tissue restoration.…”
Section: Technological Prospects Of Mxenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their robust NIR light absorption capacity and high photothermal conversion efficiency (PCE), MXenes are recognized as promising PTAs and are used widely in the researches of PTT. 21 In addition, the unique structure of MXenes endows them with high hydrophilicity, protein adsorption capacity, and good electrical conductivity, 22,23 which promote cell-matrix and intercellular interactions, indicating that MXenes have great application potential in biomedicine. For instance, many previous studies have confirmed that MXenes can promote osteogenesis in mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Skin damage is one of the most common emergencies in daily life . Skin trauma will lead to the loss of its barrier defensive function . Therefore, for the sake of repairing the wound quickly and acting as a substitute for the skin to protect the internal tissues during the wound concrescence process, it is extremely requisite to employ the wound dressing.…”
Section: Introductionmentioning
confidence: 99%